UJI HISTOKIMIA SENYAWA FLAVONOID DAN STEROID PADA TUMBUHAN PUTRI MALU (Mimosa pudica L), DAUN DUDUK (Desmodium triquetrum), KEMBANG TELANG (Clitoria ternatea), BUNGA KUPU-KUPU (Bauhinia purpurea) dan KETEPENG CINA (Cassia alata) SERTA POTENSI PENERAPAN PEMBELAJARAN BIOLOGI - Iin Ridwan; Aidil Adhani; Ibrahim Ibrahim (Biopedagogia, 2022)
Abstract: Indonesia is a country that is very rich in biodiversity which has approximately 3000 plant species that have the potential to contain bioactive compounds. One of the areas where many plants are found, namely the city of Tarakan, such as the family of plants found in the Lunto rice fields and nursery forests, namely the Fabaceae family which includes Putri Malu, Daun Duduk, Kembang Telang, Kupu-Kupu and Ketepeng Cina. In this study, the method used was histochemical test of Vanillin 4% - concentrated HCL, concentrated H2SO4 for identification of flavonoid compounds, concentrated CH3COOH and concentrated H2SO4 for identification of steroid compounds. This test was conducted to identify flavonoid and steroid compounds in each part of the leaf, stem, and root organs. The results of this study concluded that only the stem organs of the Kupu-Kupu plant were negative for flavonoid compounds and steroids as tested for ethanol extract. In this research, the potential to be implemented in biology learning is in the form of a Lesson Plan (RPP), Practical Guide, and Teaching Materials for KD 2.2 Structure and Function of Plant and Animal Tissues. Keywords: Fabaceae, Histochemical Test, Biology Learning